International Conference on Fuzzy Systems 2010
DOI: 10.1109/fuzzy.2010.5584310
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy logic applied to detect olive trees in high resolution images

Abstract: This paper tries the use of the fuzzy logic to detect olive trees in Very High Resolution Images. More concretely, fuzzy numbers are used to manage the imprecise information of the input images. A method to summarize information in a fuzzy number from data is used, and after that, the obtained fuzzy number is used to process the Very High Resolution Images by using a k-neighbor strategy. In this first approach, tested images show encouraging results because all olive trees are detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Juan et al utilized the same imagery over the application of fuzzy logic [8] and showed quite similar results as per K-Means technique. The above-mentioned techniques showed accurate results with less processing information, however lacked diversity in terms of the number of images along with the ground classes.…”
Section: Comparative Analysis With Benchmark Schemesmentioning
confidence: 85%
See 2 more Smart Citations
“…Juan et al utilized the same imagery over the application of fuzzy logic [8] and showed quite similar results as per K-Means technique. The above-mentioned techniques showed accurate results with less processing information, however lacked diversity in terms of the number of images along with the ground classes.…”
Section: Comparative Analysis With Benchmark Schemesmentioning
confidence: 85%
“…The results showed an overall omission rate of zero in six samples and a commission rate of one in six. Other methods utilized fuzzy logic, generating a fuzzy number to detect the olive trees using k-neighbor approach [8]. Promising results were obtained from the methodology showing an omission rate of one in six and a commission rate of zero.…”
Section: To Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…Juan Moreno et al used the fuzzy logic method to generate the fuzzy number and used it to process the olive trees imagery using k-neighbor approach [16]. The methodology was tested over VHR satellite imagery obtained from SIGPAC (Sistema de Informacion Geografica de parcelas agricolas) viewer of Ministry of Environment and Rural and Marine.…”
Section: Classificationmentioning
confidence: 99%
“…While hierarchical CA is widely used in olive oil research nonhierarchical (NHCA) is rarely employed. Instead, NHCA methods are heavily used in projects related to remote sensing (e.g., the detection of olive trees in satellite imagery [Moreno‐Garcia, Jiménez Linares, Rodriguez Benitez, Solana‐Cipres, ]) or sensory analysis (Pagliuca & Scarpato, ).…”
Section: Multivariate Proceduresmentioning
confidence: 99%